2017
DOI: 10.1007/s00209-017-1932-x
|View full text |Cite
|
Sign up to set email alerts
|

Infinitesimal deformations of rational surface automorphisms

Abstract: Abstract. If X is a rational surface without nonzero holomorphic vector field and f is an automorphism of X, we study in several examples the Zariski tangent space of the local deformation space of the pair (X, f ).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(266 reference statements)
0
1
0
Order By: Relevance
“…Indeed, under the condition (2), the most numerous automorphisms Bedford-Kim [1,2] and McMullen [10] constructed as realizations of Coxeter elements are those preserving cuspidal anticanonical curves. Note also that Grivaux showed that some of the automorphisms preserving cuspidal anticanonical curves are isolated in the sense that it is not possible to deform the pair (X, F ) of a surface X and an automorphism F : X → X (see [6], Theorem B). This is the reason why we consider the cuspidal anticanonical curves.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, under the condition (2), the most numerous automorphisms Bedford-Kim [1,2] and McMullen [10] constructed as realizations of Coxeter elements are those preserving cuspidal anticanonical curves. Note also that Grivaux showed that some of the automorphisms preserving cuspidal anticanonical curves are isolated in the sense that it is not possible to deform the pair (X, F ) of a surface X and an automorphism F : X → X (see [6], Theorem B). This is the reason why we consider the cuspidal anticanonical curves.…”
Section: Introductionmentioning
confidence: 99%